Hubungan Respon Inflamasi terhadap Komplikasi Kemoterapi pada Pasien Ca Mammae yang Menjalani Serial Kemoterapi di RS Ibnu Sina YW UMI: The Relationship Between Inflammatory Response and Chemotherapy Complications in Breast Cancer Patients Undergoing Serial Chemotherapy at Ibnu Sina Hospital, YW UMI - Triananda, Dhini Cesaria; Sommeng, Faisal; Mulyadi, Farah Ekawati; Juhamran, Reeny Purnamasari; Harahap, Muh. Wirawan (Jurnal Sains dan Kesehatan, 2025)
Breast cancer is a malignant disease in which abnormal breast cells grow out of control and form tumors, with the main treatments being surgery, chemotherapy, or radiotherapy. Chemotherapy is a definite treatment option for breast cancer patients, but the treatment is still not very specific, so it can cause damage to normal tissue, especially to cells that can divide rapidly. The cytotoxic effects of chemotherapy agents activate danger signals and increase inflammatory mediators, resulting in clinical complications. Inflammation is mediated by cytokines, which under normal conditions play a role in fighting infection and repairing damaged tissue. However, chemotherapy can cause cytokine dysregulation, which has a detrimental effect on body tissue with additional complications that are not caused by the cancer itself. This study was conducted to determine the relationship between the inflammatory response and complications from chemotherapy in breast cancer patients undergoing serial chemotherapy at Ibnu Sina YW UMI Hospital, by analyzing the relationship between the Systemic Inflammation Index (SII) and various clinical complications from the effects of chemotherapy. The study design used analytical observation with total sampling technique. The research subjects were patients undergoing the third cycle of chemotherapy, 56.6% of whom were over 50 years old with a low SII distribution (73.3%) and high SII (26.7%) patients. The results showed mild pain in 86.7% and no pain in 13.3% (p=0.195), nausea and vomiting (p=0.918), and leukocytosis (p=0.046). It was concluded that an increase in the Systemic Inflammation Index correlates with an increase in leukocyte levels. Keywords:          Inflammatory, chemotherapy complications, breast cancer.   Abstrak Kanker payudara adalah penyakit keganasan dimana sel - sel payudara abnormal tumbuh diluar kendali dan membentuk tumor dengan terapi utama pembedahan, kemoterapi atau radioterapi. Kemoterapi merupakan pilihan perawatan yang pasti dijalani bagi penderita Ca Mammae tetapi pengobatannya masih kurang spesifik sehingga dapat menimbulkan kerusakan pada jaringan normal khusunya pada sel tubuh yang dapat membelah dengan cepat. Efek sitotoksik agen kemoterapi akan mengaktifkan sinyal bahaya dan meningkatkan mediator-mediator inflamasi yang mengakibatkan munculnya komplikasi klinis. Inflamasi dimediasi oleh sitokin, pada kondisi normal sitokin berperan dalam melawan infeksi dan memperbaiki jaringan yang rusak. Namun, kemoterapi dapat menyebabkan disregulasi sitokin yang berdampak buruk bagi jaringan tubuh dengan komplikasi tambahan yang bukan disebabkan dari kanker itu sendiri. Penelitian ini dilakukan untuk mengetahui hubungan respon inflamasi terhadap komplikasi dari kemoterapi pada pasien Ca Mammae yang menjalani serial kemoterapi di Rumah Sakit Ibnu Sina YW UMI, dengan menganalisis hubungan antara Systemic Inflammation Index (SII) dengan berbagai komplikasi klinis dari efek kemoterapi. Desain penelitian ini menggunakan observasional analitik dengan teknik total sampling. Subjek penelitian adalah pasien kemoterapi siklus ke-3, 56,6% berusia di atas 50 tahun dengan distribusi SII rendah (73,3%),dan SII tinggi (26,7%) pasien. Hasil penelitian memperlihatkan nyeri ringan 86,7%, dan tidak nyeri 13,3% (p=0,195), mual dan muntah (p=0,918), dan leukositosis (p=0,046). Disimpulkan peningkatan Systemic Inflammation Index berkorelasi dengan peningkatan kadar leukosit. Kata Kunci:         Inflamasi, komplikasi kemoterapi, Ca Mammae